Chapter Understanding the settlement dynamics of the Ionian coastal area of Salento (Puglia, Southern Italy): the contribution of new archeological data from the fortified Messapian centre at Li Schiavoni - Cera, Giovanna (Proceedings e report, 2020)
Located about 4 km northeast of the Ionian coast, the small fortified Messapian settlement at Li Schiavoni (Puglia, Southern Italy) occupy an extensive plateau, controlling the territory. The stratigraphic research has revealed part of a house, remains of burials and some sections of the fortification wall. The walls, built during the Archaic period, was restored and reinforced during the Hellenistic Age, perhaps because of an imminent threat. Thanks to the special focus on the new archaeological data from the Li Schiavoni settlement, we can highlight some aspects related to the settlement system on the Ionian coast of the Salento (Puglia, Southern Italy).